Ets-2 Acts As a Transcriptional Repressor of the Human Immunodeficiency Virus Type 1 through Binding to a Repressor–Activator Target Sequence of 5′-LTR - Panagoulias, Ioannis; Karagiannis, Fotios; Aggeletopoulou, Ioanna; Georgakopoulos, Tassos; Argyropoulos, Christos P.; Akinosoglou, Karolina; Gogos, Charalambos; Skoutelis, Athanasios; Mouzaki, Athanasia (Frontiers in Immunology, 2018)
HIV-1 is transcriptionally active in activated T helper (Th)-cells and inactive in naive or resting memory Th-cells. Ets-2 is a pre-induction transcriptional repressor of the IL-2 gene in naive Th-cells and a candidate transcriptional repressor of HIV-1 in the same cells, because the -279 to -250 upstream region of HIV-1-LTR (RATS, Repressor-Activator-Target-Sequence), that participates in HIV-1-LTR transcriptional silencing, encompasses the AAGGAG Ets-2 binding site. In this proof of concept study, we investigated whether Ets-2 represses the expression of HIV-1. To assess whether Ets-2 can repress HIV-1 transcriptional activation acting through RATS, we transfected Jurkat cells with an Ets-2 overexpression plasmid (pCDNA3-ets-2) or Ets-2 silencing plasmids (ets-2-shRNA) and, as target genes, plasmids carrying the whole HIV-1-LTR sequence (HIV-1-LTR-CAT) or two copies of the RATS sequence (2xRATS-CAT) or a point mutation in the Ets-2 binding site (2xmutantRATS-CAT) or CMV-CAT (control). Ets-2 overexpression resulted in a significant reduction of HIV-1-LTR-CAT and 2xRATS-CAT activities in stimulated cells, but not of the 2xmutantRATS-CAT or CMV-CAT. Ets-2 silencing led to increased activities of HIV-1-LTR-CAT and 2xRATS-CAT in unstimulated cells, but had no effect on the activities of 2xmutantRATS-CAT and CMV-CAT. To assess Ets-2 binding to HIV-1-LTR-RATS in naive Th-cells, we isolated naive Th-cell nuclear proteins and passed them through an Ets-2 antibody column; EMSAs were performed using a RATS probe mixed with consecutive protein eluates. Ets-2 bound to the HIV-1-LTR-RATS in a dose-dependent manner. To assess Ets-2 binding to RATS in vivo, Jurkat cells were transfected with 2xRATS-CAT and stained for the Ets-2 protein and the RATS sequence by combining immunofluorescence and FISH techniques. In unstimulated cells, Ets-2 bound to RATS, whereas no binding was observed in stimulated cells. To test for RATS specificity, the same experiments were performed with 2xmutantRATS-CAT and no binding of Ets-2 was observed. The results were corroborated by ChIP assays performed with the same cells. Our results show that Ets-2 is a transcriptional repressor of HIV-1. Repression of HIV-LTR-RATS mediated by Ets-2 may account for the low-level transcription and replication of HIV-1 in naive Th-cells, and contribute to the viral latency and maintenance of viral reservoirs in patients, despite long-term therapy.